Pemberian Tunjangan Khusus Daerah Terpencil untuk Perbaikan Kinerja Guru SMP di Kecamatan Liukang Tupabbiring Utara Kabupaten Pangkep - M. Ziaul Haq Hs (IAIN PAREPARE, 2018)
ABSTRACTTeacher is one of the crucial factors in learning; regardless how ideal thecurriculum is, without any support of teachers’ capability to implement thecurriculum, it would not achieve the assigned educational goals. Teachers whodevote themselves in areas categorized as 3T (Outermost, Frontier, andUnderdeveloped) require concerns from the government. The study aims to explain(1) How the provision of special allowances of remote areas to the junior highschool teachers in the District of Northern Liukang Tupabbiring of PangkepRegency, (2) How the performance of junior high school teachers in the District ofNorthern Liukang Tupabbiring of Pangkep Regency, (3) What impacts of providingspecial allowances of remote areas on the improvement of junior high schoolteachers’ performance in the District of Northern Liukang Tupabbiring of PangkepRegency.The study was a field research situated in junior high schools in the District ofNorthern Liukang Tupabbiring of Pangkep Regency. The research subjects werejunior high school teachers in the District of Northern Liukang Tupabbiring ofPangkep Regency. Interview, observation, and documentation were utilized incollecting the data which then verified by reducing the data, presenting them, anddrawing conclusions. The study employed a multidisciplinary approach usingqualitative data analysis consisting of three stages: (1) pre-field, (2) field work, (3)analysis.The results revealed that the provision of special allowances of remote areas to thejunior high school teachers in the District of Northern Liukang Tupabbiring ofPangkep Regency was still not evenly distributed. Most of the teachers, however,had got the allowances, while the junior high school teachers’ performance in theDistrict of Northern Liukang Tupabbiring of Pangkep Regency needed to beimproved, and after giving the allowance, they were motivated to developthemselves and their performance as teachers in remote areas. The impacts ofproviding special allowances of remote areas in improving the junior high schoolteachers’ performance in the District of Northern Liukang Tupabbiring of PangkepRegency were as an additional income to overcome the difficulties of life forserving in remote areas, to boost the teachers' welfare in remote areas, so thequality of education in remote areas could compete with the education in urbanareas. The implications of this study were teachers expected that there were equitabledistribution to all teachers who were entitled to special allowances in remoteareas, as well as providing them with the ease of continuing education to improvetheir competence in order to become creative and insightful teachers.